Experimental Evaluation of Tactile Sensors for Compliant Robotic Hands - Friedl, Werner A.; Roa, Máximo A. (Frontiers in Robotics and AI, 2021)
The sense of touch is a key aspect in the human capability to robustly grasp and manipulate a great variety of objects. Despite many years of development, there is still no preferred solution for tactile sensing in robotic hands: Multiple technologies are available, each one with different benefits depending on the application. This paper compares the performance of different tactile sensors mounted on the variable stiffness gripper CLASH 2F, including three commercial sensors: a single taxel sensor from the companies Tacterion and Kinfinity, the Robotic Finger Sensor v2 from Sparkfun, plus a self-built resistive 3x3 sensor array, and two self-built magnetic 3-DoF touch sensors, one with 4 taxels and one with 1 taxel. We verify the minimal force detectable by the sensors, test if slip detection is possible with the available taxels on each sensor, and use the sensors for edge detection to get the orientation of the grasped object. To evaluate the benefits obtained with each technology, and to assess which sensor fits better the control loop in a variable stiffness hand, we use the CLASH gripper to grasp fruits and vegetables following a published benchmark for pick and place operations. To facilitate the repetition of tests, the CLASH hand is endowed with tactile buttons that ease human-robot interactions, including execution of a predefined program, resetting errors, or commanding the full robot to move in gravity compensation mode.